2020
DOI: 10.1101/2020.02.08.939462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data-driven models reveal mutant cell behaviors important for myxobacterial aggregation

Abstract: Single mutations frequently alter several aspects of cell behavior but it is often not clear whether a particular statistically significant change is biologically significant. To determine which behavioral changes are most important for multicellular self-organization, we devised a new methodology using Myxococcus xanthus as a model system. During development, myxobacteria coordinate their movement to aggregate into spore-filled fruiting bodies. We investigate how aggregation is restored in two mutants, csgA a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Calculating the reversal bias in a 1 hour moving window, we found that it was positive throughout initial aggregation (Fig. S1A purple lines), indicating that cells bias their persistent movement towards aggregates as found previously (35,36). We then quantified the strength of the traffic jam effect using the 8 difference in persistent speeds, transition probabilities into the non-persistent state, and the durations of the non-persistent state between cells inside versus outside aggregates (Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Calculating the reversal bias in a 1 hour moving window, we found that it was positive throughout initial aggregation (Fig. S1A purple lines), indicating that cells bias their persistent movement towards aggregates as found previously (35,36). We then quantified the strength of the traffic jam effect using the 8 difference in persistent speeds, transition probabilities into the non-persistent state, and the durations of the non-persistent state between cells inside versus outside aggregates (Fig.…”
Section: Resultssupporting
confidence: 64%
“…Over the next 5-7 hours, cells build sequential layers that develop into the main mass of the nascent fruiting body. During this phase, several cell behaviors contribute to the growth of initial aggregates (35,36). One of these behaviors is a density-dependent trafficjam effect, which slows down movement in high-density regions and increases the likelihood of cells entering a stopped state.…”
Section: Introductionmentioning
confidence: 99%
“…The uniquely multicellular lifestyles of myxobacteria have motivated continued efforts to explore the myxobacterium Myxococcus xanthus as a model organism for cooperative behaviours including development (Islam et al ., 2020; Sharma et al ., 2021), motility (Mercier et al ., 2020; Rendueles and Velicer, 2020; Zhang et al ., 2020b), and predation (Thiery and Kaimer, 2020; Zhang et al ., 2020a; Sydney et al ., 2021). Often attributed to their need to acquire nutrients as generalist predators (Nair et al ., 2019) and capacity to prey upon clinical pathogens (Livingstone et al ., 2017), myxobacteria have also been a valuable resource for the discovery of novel specialized metabolites as potential therapeutic lead compounds (Herrmann et al ., 2017; Baltz, 2019; Perez et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The uniquely multicellular lifestyles of myxobacteria have motivated continued efforts to explore the myxobacterium Myxococcus xanthus as a model organism for cooperative behaviors including development (Islam et al, 2020; Sharma et al, 2021), motility (Mercier et al, 2020; Rendueles and Velicer, 2020; Zhang et al, 2020b), and predation (Thiery and Kaimer, 2020; Zhang et al, 2020a; Sydney et al, 2021). Often attributed to their need to acquire nutrients as generalist predators (Nair et al, 2019) and capacity to prey upon clinical pathogens (Livingstone et al, 2017), myxobacteria have also been a valuable resource for the discovery of novel specialized metabolites as potential therapeutic lead compounds (Herrmann et al, 2017; Baltz, 2019; Perez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%